Migrant wealth in Germany - Rudolf Faininger; Svenja Flechtner (The Journal of Economic Inequality, 2025)
Migrant households in Germany hold significantly less wealth than native households, with disparities varying by origin and generation. Using SOEP data (2012, 2017), this study quantifies gaps across the wealth distribution and examines income, saving rates, and portfolio composition. Migrants from low- and middle-income countries exhibit the largest gaps, with persistent disadvantages in the upper distribution. Second-generation high-income country migrants show signs of convergence. Disparities are mainly due to portfolio composition and differences in earnings and savings behavior. The findings underscore the heterogeneity of migrant wealth accumulation and contribute to research on wealth inequality and migration economics.
Keywords: 300; Wealth gap; Migrants; RIF decomposition; Germany; Socio-Economic Panel (SOEP)